Time Waste Identification Using Value Stream Mapping in Wood Manufacturing - Faridah, Cucu; Lestari, Yuliani Dwi (Journal of Business and Management, 2016)
Abstract. This paper aims to describe the application of Value stream mapping to identify the time in the barecore product realization process in PT.XYZ. In addition to identifying time, value stream mapping can discover some wastes that occur in the product realization process. The waste found is made as the basis for maintenance. This study was conducted with several stages. The first stage is to conduct current mapping to depict the actual conditions in the product realization process. The second phase is to analyze current value stream mapping with the data demand 40 container in September utill November. It is found that there is difference in the execution time of the process, so the waste that causes it and how to solve the problem will be analised. The future state mapping is the last step in this study, and it is found in this step that there is time reduction in the barecore product realization process. The use of value stream mapping application in this study managed to finding wastes that occur in the barecore product realization process. Waiting time are the processes by which all the divisions in the product realization process experience. Objective to find solution for eliminating waste. This study found a solution that can reduce waste. The email that will be used in the process of reporting documents. A system of electronic signature that will accelerate the process which requires ratification documents needed. Reporting is a multiplication reporting system, where the presence of this multiplication system will make the fulfillment of some process completed rapidly. The Follow-up process is one of the alternatives process of company that is always waiting for the requested process comes into its own. So with the minimum limit of the follow-up, it will accelerate the next process to be done. Future value stream mapping that is created reduces the use of time that occurs within the product realization process. It is observed, in the process of product realization with demand 40 container could reduce the time by 0.58 days.Â Keyword: Value Stream Mapping (VSM), Process Mapping, Lean, Waste.